Antibacterial Properties of Local Malaysian Trigona Sp. Honey Towards Different of Pathogenic Bacteria in Vitro - Shalsh, Fawzia Jassim; Khalaf, Ahmed Mohammed; Hafiz, Mohammed; Ali, Imad Ibrahim (Diyala Agricultural Sciences Journal, 2021)
Honey is one of the oldest natural medicines known with a very high therapeutic value. Nowadays, in the medical field, several important therapeutic effects of honey have been elucidated. This study was conducted to reveal the antimicrobial activity of the commercially available local Malaysian Trigona sp. honey towards different pathogenic bacteria specifically Staphylococcus aureus, Streptococcus pyogenes, Escherichia coli, and Salmonella typhimurium. The Minimum inhibitory concentration and Minimum bactericidal concentration were determined by the disc-diffusion test and agar well diffusion test. Different concentration of the honey was tested in the disc-diffusion and agar well diffusion test. The results of these tests were in terms of Inhibition zone diameter. The results obtained from the current study are the dilution of different concentration of honey from Trigona sp. are very significant because the only net concentration of both of honey Trigon a sp. possessed antimicrobial properties in term of Minimum inhibitory concentration) and Minimum bactericidal concentration. The result also can say that Trigona sp. honey possessed antibacterial properties and can be used as alternative medicine in the veterinary field in the future